IR-images of PV-modules with potential induced degradation (PID) correlated to monitored string power output - Buerhop, Claudia; Pickel, Tobias; Blumberg, Tiberius; Adams, Jens; Wrana, Simon; Dalsass, Manuel; Zetzmann, Cornelia; Camus, Christian; Hauch, Jens; Brabec, Christoph (Reliability of Photovoltaic Cells, Modules, Components, and Systems IX, 2016)
Many PV-plants suffer from potential induced degradation (PID) which causes severe power reduction of installed PVmodules. Fast and reliable methods to detect PID and evaluate the impact on the module performance are gaining importance. Drone-Assisted IR-inspection is a suitable method. PID affected modules are detected by their characteristic IR-fingerprint, modules with differing number of slightly heated cells occur more frequently at the negative string end. These modules show a degraded IV-curve, lowered Voc and Isc, and electroluminescence (EL)-images with suspicious, dark cells. Also, the measured string power is reduced. For a first quantitative data evaluation the suspicious cell are counted in the IR-images and correlated with the module power. A linear decrease of the module power with increasing number of suspicious cells results. A correlation function for estimating the module power was deduced, which has a mean deviation of less than 7%. This correlation function allows an acceptable approximation of the string power.
Keywords: Degradation; Electroluminescence; IR-imaging; IR-inspection; PID; Potential Induced Degradation; PV-modules; PV-plants; Reliability